Potentiometric Determination of stepwise Formation Constants of Mn(II), Fe(II), Fe(III), Co(II), Co(III) and Cu(II) Chelates with 1,4,7-Triazacyclononane - Belal, A.A.M.; Amrallah, A.H.; D. Peacock, Robert (Asian Journal of Chemistry, 2010)
Proton-ligand dissociation constant of 1,4,7-triazacyclononane (H3[9]aneN3)3+ and the stability constants of its chelates with Mn(II), Fe(II), Fe(III), Co(II), Co(III) and Cu(II) have been determined pH-metrically in aqueous solution in the presence of 0.1 M NaNO3 at 20º–32ºC. The thermodynamic parameters for the mono- and bis- complexes under investigation are also evaluated.